University faculty and information literacy - Donna L. Whitson; Donna D. Amstutz (Adult Education Research Conference, 1996)
This descriptive study surveyed faculty and academic professionals at the University of Wyoming and looked at the ways in which faculty acquire the information they need and the ways in which they require or encourage students to access and use information. The findings describe the characteristics and roles of faculty who use technology for information access and describe how and what resources they use. Recommendations for further investigation are made.